Implementation of Project-Based Learning in Increasing the Concern of Class V Students of SDN 3 Tanjung towards Environmental Damage in Science Learning - Dwi Rela Abdillah Khabib; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
Implementation of Project-Based Learning in Increasing Awareness of Fifth Grade Students of SDN 3 Tanjung towards Environmental Damage in Science Learning. This study aims to describe the implementation of the Project-Based Learning (PjBL) model in learning the theme of environmental damage in fifth grade students of SDN 3 Tanjung and analyze the increase in students' awareness of environmental damage after the implementation of the PjBL model. The research method used was a quasi-experimental with a one group pretest-posttest design. The subjects of the study were all fifth grade students of SDN 3 Tanjung, totaling 25 people. The research instruments included an environmental awareness attitude questionnaire, student involvement observation sheets, and a project product assessment rubric. Data analysis used descriptive statistics and paired sample t-test. The results showed a significant increase in students' awareness of the environment after the implementation of PjBL, indicated by an increase in the average score from 64.8 (pretest) to 81.2 (posttest) and a significance value of p <0.05. Thus, the implementation of Project-Based Learning is effective in increasing students' awareness of environmental damage.